EXAMINING SHARIA-BASED FINANCIAL PRODUCT INNOVATION FROM A GEN Z PERSPECTIVE: A CASE STUDY OF ISLAMIC ECONOMICS AND BUSINESS STUDENTS AT IAIAN - Siti Chasanah (Jurnal Dinamika Ekonomi Syariah, 2026)
This study explores the perspectives of Generation Z regarding Sharia-based financial product innovations, focusing on Islamic Economics and Business students at IAIAN. Employing a descriptive qualitative approach, this research maps the prospects, barriers, and the depth of student comprehension concerning the modernization of the Islamic financial sector within the digital sphere. Empirical findings indicate that digitalization offers expansive opportunities to introduce Sharia financial products tailored to Gen Z's preferences, including peer-to-peer (P2P) lending, crowdfunding, and mobile-based investment instruments. Nevertheless, the sector still encounters classic obstacles, such as low Sharia financial literacy, digital access disparities, and complex regulatory frameworks. On the other hand, the students, as the core subjects of this study, demonstrate both a mature understanding and tangible contributions through research activities, internship programs, and public education initiatives. This research underscores that a synergistic integration between Sharia financial industry players and Generation Z plays a crucial role in fostering innovations that are highly adaptive to technological advancements while remaining strictly compliant with Sharia principles